Monocytes and T cells incorporated in full skin equivalents to study innate or adaptive immune reactions after burn injury - Mulder, Patrick P.G.; Vlig, Marcel; Elgersma, Anouk; Rozemeijer, Lotte; Mastenbroek, Leonore S.; Middelkoop, Esther; Joosten, Irma; Koenen, Hans J.P.M.; Boekema, Bouke K.H.L. (Frontiers in Immunology, 2023)
Thermal injury often leads to prolonged and excessive inflammation, which hinders the recovery of patients. There is a notable absence of suitable animal-free models for investigating the inflammatory processes following burn injuries, thereby impeding the development of more effective therapies to improve burn wound healing in patients. In this study, we established a human full skin equivalent (FSE) burn wound model and incorporated human peripheral blood-derived monocytes and T cells. Upon infiltration into the FSEs, the monocytes differentiated into macrophages within a span of 7 days. Burn-injured FSEs exhibited macrophages with increased expression of HLA-DR+ and elevated production of IL-8 (CXCL8), in comparison to uninjured FSEs. Among the T cells that actively migrated into the FSEs, the majority were CD4+ and CD25+. These T cells demonstrated augmented expression of markers associated with regulatory T cell, Th1, or Th17 activity, which coincided with significant heightened cytokine production, including IFN-γ, IL-4, IL-6, IL-8, IL-10, IL-12p70, IL-17A, IP-10 (CXCL10), and TGF-β1. Burn injury did not impact the studied effector T cell subsets or cytokine levels. Collectively, this study represents a significant advancement in the development of an immunocompetent human skin model, specifically tailored for investigating burn-induced innate or adaptive immune reactions at the site of burn injury.